Long-term continuous no-till corn-soybean systems: Examining soil carbon sequestration and nitrogen accumulation across various pools - Maninder K. Khosa; Kenan Barik; Ekrem Aksakal; Mohammad MR. Jahangir; Nataliia O. Didenko; Khandakar R. Islam (PLoS ONE, 2025)
Tillage practices influence the soil’s capacity as either a sink or source of carbon (C) within agroecosystems. The objective of the study was to assess the effects of no-till (NT) management over 0, 6, 20, and 35 years in a rainfed corn (Zea mays)–soybean (Glycine max) system, incorporating cereal rye (Secale cereale L.) as a cover crop, on soil organic C (SOC) sequestration and total N accumulation across different pools. The results showed significant increases under NT compared to conventional tillage (CT), including SOC (14–69%), total N (16–60%), microbial biomass C (SMB; 44–101%), active C (11–33%), passive C (15–72%), particulate organic C (POC; 43–173%), and particulate organic N (PON; 29–135%). While NT exhibited higher basal respiration (BR) rates, it significantly reduced C loss via the metabolic quotient, calculated as specific maintenance respiration (qCO2), by 7.9–29.4% compared to CT. Ratios of passive C to active C increased under long-term NT, indicating a higher accumulation of stable SOC fraction, which consequently reduced soil bulk density (ρb) compared to CT. Using the fixed depth approach, SOC, SMB, active C, and POC were sequestered at rates of 587.4 ± 134.1, 10.1 ± 4.1, 5.3 ± 1.8, and 382.2 ± 55 kg ha ⁻ ¹ yr ⁻ ¹ in the 0–15 cm depth, and at 1.6 ± 0.5, 4.1 ± 1.4, 54 ± 8, and 192 ± 64 kg ha ⁻ ¹ yr ⁻ ¹ in the 15–30 cm depth. Likewise, total N and PON accumulation rates were 72.2 ± 18.4 and 14.1 ± 5.5 kg ha ⁻ ¹ yr ⁻ ¹ at 0–15 cm, and 15 ± 5 and 4.3 ± 1.6 kg ha ⁻ ¹ yr ⁻ ¹ at 15–30 cm. Similar but variable rates of SOC sequestration and total N accumulation were observed at both depths when using the equivalent mass approach compared to the fixed depth method. Adjusting for soil mass equivalence to account for ρb variability in fixed depths provides a more realistic estimation of SOC and total N stocks in different pools, as the fixed depth approach tends to overestimate these stocks. Our findings demonstrate that long-term NT consistently facilitates SOC sequestration and total N accumulation in different pools, with these benefits distributed non-linearly across distinct SOC and total N pools at the 0–15 cm depth and linearly at the 15–30 cm depth in rainfed corn-soybean systems.